Analisis Faktor yang Mempengaruhi Keputusan Investasi Generasi Muda di Kota Samarinda - Sarani Putri Jamdi; Ratna Fitri Astuti; Reza Reza; Sudarman Sudarman; Noor Ellyawati (Jayapangus Press, 2026)
The advancement of digital technology and easy access to various investment instruments have driven increased participation by the younger generation in investment activities. However, sound investment decisions depend not only on the desire for profit but are also influenced by various factors underlying the decision-making process. This study aims to analyze the factors shaping the investment decisions of the younger generation in Samarinda City. A quantitative approach with an explanatory research design was employed. The sample consisted of 96 young individuals aged 15–30 with prior investment experience, selected using purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) with LISREL 10.20 software. The results indicate that the measurement model met goodness-of-fit criteria following model respecification, yielding 21 valid indicators that constitute the research constructs. Factor analysis identified four primary factors shaping the investment decisions of the younger generation in Samarinda City: setting investment goals, determining investment policies, selecting portfolio and asset strategies, and measuring and evaluating portfolio performance. These findings contribute to an understanding of the key dimensions underlying the investment decisions of the younger generation and highlight the importance of strengthening financial literacy and investment education, enabling young people to make investment decisions that are more rational, well-planned, and oriented toward long-term financial goals.